Модель визначення обсягів залучення субпідряду в умовах використання обмежених ресурсів організації-виконавця - Доненко, В. І.; Грін, О. О.; Тімощук, Д. В. (Ways to Improve Construction Efficiency, 2012)
The paper proposed a model of determining the value of amounts of specialized subcontracting services to ensure efficient use of the limited resources of the organization. It allows you to efficiently allocate limited resources on critical areas of the organization works to identify their organizational and technological parameters.